Jan Kiepura. (Gdańsk : [s.n., 1958)
Afisz inf. o występach Jana Kiepury w gdańskiej Stoczni 22.10.1958 r.
Keywords: Kiepura, Jan -- (1902-1966) -- druki ulotne; Stocznia Gdańska -- 1945-1970 -- druki ulotne; Życie muzyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- życie artystyczne